The Convergence of World Prosperity and Afterlife Salvation: Neoliberalism and Political Islam in Turkey - Firmansyah, Muhammad Andi (UI Scholars Hub, 2025)
This article investigates why Turkey’s middle-to-low-income earners, the segment of the population that has suffered the most from the neoliberal policies of the Adalet ve Kalkınma Partisi (Justice and Development Party AKP), have continued to support the party for so long. Using a case study approach based on secondary data, this article argues that the source of the AKP’s enduring legitimacy lies in their skill in utilising political Islam to consolidate neoliberalism. They strategically framed neoliberal restructuring in an Islamic spirit, generating not only loyal cross-class support but also obedience to neoliberal political projects with all their destructive consequences. The AKP, for example, justifies material inequality not as a logical consequence of meritocracy as in secular neoliberalism but rather as a divine decree that determines the individual’s path of salvation and social role. In this way, the AKP government gains prerogatives and legitimacy that secular neoliberal states rarely enjoy. However, this model of hegemony is also fragile and unsustainable. Since the economic slowdown in 2012 and a series of critical incidents, the AKP government has faced a profound legitimacy crisis. Eventually, it took the path of authoritarianism as a survival strategy. This research enriches our understanding of how neoliberalism can adapt and blend discursively with local socio-political culture. In particular, the AKP case serves as a good reminder that responding to neoliberal crises with more neoliberalism often only postpones problems rather than solving them.